2021
DOI: 10.1007/s00068-021-01756-3
|View full text |Cite
|
Sign up to set email alerts
|

Open versus minimally invasive fixation of thoracic and lumbar spine fractures in patients with ankylosing spinal diseases

Abstract: Purpose Posterior multilevel fixation of traumatic instability in ankylosing spinal disease (ASD) can be performed by open surgery (OS) or minimally invasive surgery (MIS). We investigated whether both methods differ based on the reduction results and perioperative parameters. Methods In this retrospective cohort study, OS and MIS groups were investigated. The bisegmental Cobb angles and dislocation angles were measured using pre- and postoperative CT imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…Considering the 157 patients treated with short-segmental posterior stabilization, the majority of surgeries were performed via MIS. This is in accordance with the recommendations published in the literature based on the lower morbidity and lower blood loss associated with MIS [24][25][26]. The dominant treatment strategy in the included patients was hybrid stabilization, including posterior shortsegmental stabilization and cement augmentation of the fractured vertebral body.…”
Section: Discussionsupporting
confidence: 84%
“…Considering the 157 patients treated with short-segmental posterior stabilization, the majority of surgeries were performed via MIS. This is in accordance with the recommendations published in the literature based on the lower morbidity and lower blood loss associated with MIS [24][25][26]. The dominant treatment strategy in the included patients was hybrid stabilization, including posterior shortsegmental stabilization and cement augmentation of the fractured vertebral body.…”
Section: Discussionsupporting
confidence: 84%
“…3 Preoperative computed tomography (CT) scan in the sagittal plane and lateral intraoperative radiographs depicting complete, closed reduction of fracture. with thoracic or lumbar fractures in the setting of AS and found significantly decreased average operative time, intraoperative blood loss, and length of postoperative hospital stay using minimally invasive techniques, without any difference in quality of reduction or accuracy of screw placement (Table I) 11,24,25,[30][31][32][33] . Finally, percutaneous screw placement in the setting of a deformed spine may be challenging because traditional landmarks used to guide safe implant placement may be distorted or absent 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, surgery should be kept as short as possible. Vanderschot et al reported a mean operation time of 60 min for the implantation of a single transsacral rod in 19 patients [16]. In our cohort of 24 geriatric patients, the insertion of two transsacral bars took an average of only 72 min.…”
Section: Discussionmentioning
confidence: 55%
“…This includes adequate fracture stabilisation for sufficient relief of symptoms. At the same time, surgical invasiveness and perioperative blood loss should be kept to a minimum to prevent haemorrhagic circulatory depression with resulting organ dysfunction such as prerenal renal failure [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation